Effects of dietary lipid level on growth, fatty acid profiles, antioxidant capacity and expression of genes involved in lipid metabolism in juvenile swimming crab, Portunus trituberculatus. Issue 2 (28th January 2020) - Sun, Peng; Jin, Min; Jiao, Lefei; Monroig, Óscar; Navarro, Juan Carlos; Tocher, Douglas R.; Betancor, Mónica B.; Wang, Xuexi; Yuan, Ye; Zhou, Qicun
Abstract: The regulation of lipogenesis and lipolysis mechanisms related to consumption of lipid has not been studied in swimming crab. The aims of the present study were to evaluate the effects of dietary lipid levels on growth, enzymes activities and expression of genes of lipid metabolism in hepatopancreas of juvenile swimming crab. Three isonitrogenous diets were formulated to contain crude lipid levels at 5·8, 9·9 and 15·1 %. Crabs fed the diet containing 15·1 % lipid had significantly lower growth performance and feed utilisation than those fed the 5·8 and 9·9 % lipid diets. Crabs fed 5·8 % lipid had lower malondialdehyde concentrations in the haemolymph and hepatopancreas than those fed the other diets. Highest glutathione peroxidase in haemolymph and superoxide dismutase in hepatopancreas were observed in crabs fed 5·8 % lipid. The lowest fatty acid synthase and glucose 6-phosphate dehydrogenase activities in hepatopancreas were observed in crabs fed 15·1 % lipid, whereas crabs fed 5·8 % lipid had lower carnitine palmitoyltransferase-1 activity than those fed the other diets. Crabs fed 15·1 % lipid showed lower hepatopancreas expression of genes involved in long-chain-PUFA biosynthesis, lipoprotein clearance, fatty acid uptake, fatty acid oxidation, lipid anabolism and lipid catabolism than those fed the other diets, whereas expression of some genes of lipoprotein assembly and fatty acid oxidation was up-regulated compared with crabs fed 5·8 % lipid. Overall, high dietary lipid level can inhibit growth, reduce antioxidant enzyme activities and influence lipid metabolic pathways to regulate lipid deposition in crab.